(untitled) (Research, Society and Development, 2025)
The search for effective and regenerative aesthetic treatments has driven the use of exosomes in dermatological procedures. This study aims to present a case report demonstrating the application and results of the use of exosomes containing PDRN in facial aesthetics. A patient underwent microneedling associated with the application of exosomes with PDRN for facial rejuvenation. Three intervention sessions were performed at 30-day intervals, using a standardized intradermotherapy protocol. The results showed improvement in skin quality, with increased vitality, reduction of fine lines, and more uniform texture. The study suggests that PDRN-containing exosomes represent a promising strategy in regenerative aesthetics, although further studies are needed to consolidate their clinical efficacy.